Pengaruh Motivasi, Disiplin, dan Beban Kerja terhadap Kinerja Pegawai pada BLU UPTD Trans Semarang - Putri Maharani Setyowati; Heri Usodo (Lembaga Pengembangan Kinerja Dosen, 2026)
Employee performance is a key determinant of organizational effectiveness in delivering high-quality public services. This study aims to analyze the effects of motivation, work discipline, and workload on employee performance at BLU UPTD Trans Semarang. A quantitative approach was employed involving all administrative employees as the research population. Using a saturated sampling technique, 100 respondents were included in the study. Data were collected through structured questionnaires and analyzed using multiple linear regression with the least squares method. The findings indicate that motivation, work discipline, and workload each have a positive and significant effect on employee performance. Simultaneously, these three variables also exert a positive and significant influence on employee performance, demonstrating that employee performance is shaped by both individual and organizational factors. Higher motivation encourages employees to perform their duties more effectively, while strong work discipline promotes responsibility, punctuality, and adherence to organizational procedures. Appropriate workload management also enables employees to complete their tasks efficiently without reducing productivity or service quality. These findings imply that organizations should strengthen employee motivation, enforce work discipline consistently, and manage workloads proportionally to improve overall performance. Implementing these strategies is expected to enhance organizational effectiveness, optimize human resource management, and support the delivery of more efficient, responsive, and high-quality public services for the community.